The Impact of Guangyuan Forest Health Tourism Industry Development Strategy on Sichuan Tourist Intention - Yuting Zhang; Jacky Mong Kwan Watt (International Forum of Researchers and Lecturers, 2025)
The abstract of the Guangyuan Forest Health Tourism Industry Development Strategy focuses on enhancing tourist intentions in Sichuan through a multifaceted approach. The strategy emphasizes the importance of targeted marketing that highlights the health benefits of forest tourism, utilizing digital platforms and social media to reach health-conscious travelers effectively. Integrating cultural experiences with natural attractions is crucial, as well as fostering emotional connections and encouraging repeat visits. Sustainability practices are prioritized to build consumer trust and align with environmentally conscious travel trends. The strategy also calls for improving visitor experiences through enhanced infrastructure, immersive activities, and continuous feedback mechanisms to refine offerings. Establishing partnerships with local businesses and cultural organizations further enriches the tourism experience, contributing to the sustainable growth of the forest health tourism sector in Guangyuan and enhancing overall tourist satisfaction based on a sample of 385 Sichuan respondents.